Blockchain-based electronic Bill of lading : Potentials and Challenges - Nguyen, Ha Mi; Černá, Iveta, 1979-; Rožek, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The aim of this bachelor’s thesis is to evaluate aspects of an electronic bill of lading based on blockchain technology with a focus on its differences from a traditional bill of lading in paper form. This thesis aims to evaluate its potential benefits and challenges for companies to adopt in international trade while also giving insights into an example of a current practical implementation of the blockchain technology in context with electronic bill of lading such as FIATA e-FBL.
Vedoucí práce: Iveta Černá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses